2016
DOI: 10.1590/0102-3772e32223
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do Conhecimento sobre Trauma Craniano Violento por Pais Brasileiros

Abstract: ResumO -A ocorrência do trauma craniano violento (TCV) pode estar associada à falta de conhecimento de pais e cuidadores sobre o desenvolvimento infantil. Neste sentido, o presente estudo pretendeu investigar o conhecimento de pais sobre o choro do bebê, as estratégias para lidar com o choro e as consequências de sacudi-lo. Participaram da pesquisa 83 mães e 7 pais de recém-nascidos, que responderam ao instrumento Questionário sobre o Choro do Bebê. Os resultados do estudo sugerem um desconhecimento por parte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In addition, 34,4% didn´t know that shaking could cause serious consequences for the child. That clarifies the need of prevention strategies aimed at parents [43].…”
Section: Prevention Education and Trainingmentioning
confidence: 84%
“…In addition, 34,4% didn´t know that shaking could cause serious consequences for the child. That clarifies the need of prevention strategies aimed at parents [43].…”
Section: Prevention Education and Trainingmentioning
confidence: 84%
“…Runyan et al (2010), observed that among 813 mothers interviewed in Embu, São Paula State, 10% reported having shaken their child under 2 years of age in the last year. In the study by Lopes and Williams (2016a) it was observed that 34% of the 90 parents interviewed in a municipality in the interior of the State of São Paulo reported that they would shake their babies to stop them crying. Finally, in the study by Fernandes, Silva and Javorski (2010), it was verified that 60% of 142 professionals of the Family Health Team of a municipality in the interior of Pernambuco State reported having previously shaken a baby.…”
mentioning
confidence: 99%